Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Kingdom of the Netherlands concerning Border Controls on Rail Traffic between the Netherlands and the United Kingdom using the Channel Fixed Link, The Hague, 10 July 2020. ([2020-08-13]) - Unknown
No abstract available